Application of the thin-wire integral representation of the electromagnetic field to solving the problem of diffraction of electromagnetic waves on conducting bodies - Dmitry P. Tabakov; Sergey V. Morozov; Dmitriy S. Klyuev (Физика волновых процессов и радиотехнические системы, 2022)
The article is devoted to numerical methods for solving the problem of diffraction of electromagnetic waves by conducting bodies. Two approaches to solving the problem are considered. The first one is based on the use of the thin-wire integral representation of the electromagnetic field (TP-method) for a grid model of the body surface. The second approach is associated with the use of the basis functions of RaoWiltonGlisson when solving a vector integral equation formulated with respect to the electric current density on the body surface (RWG-method). The diffraction of a plane linearly polarized electromagnetic wave by a sphere is considered as a test problem. The results of calculations of the normalized diagrams of the scattered field are presented. It is shown that there are practically no visual differences for the results obtained using both approaches. At the same time, it should be noted that the TP method is much simpler in numerical implementation than the RWG method.